2011
DOI: 10.1007/s00296-011-1947-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rsa polymorphism of the estrogen receptor-β gene with rheumatoid arthritis

Abstract: To investigate the possible influence of the single nucleotide polymorphism (SNP) of the estrogen receptor-β gene, rs1256049 (Rsa) in exon 5, on the frequency of rheumatoid arthritis (RA), 263 RA patients and 174 control subjects with osteoarthritis (OA) were recruited. Rsa polymorphism was detected using a PCR-RFLP, Polymerase Chain Reaction-Restriction Fragment Length Polymorphism method. The occurrence of both mutant allele (G) and genotype (GG) were significantly higher in RA than in OA patients (allele P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…Because this evaluation is primarily dependent on the stages and progress of joint deterioration (e.g., mild or rapid, and oligo arthritis or multi joint), classifications of disease severity are not influenced by differences in sensitivity to drug treatment. Most of the patients enrolled in this study were classified as MES RA, which was consistent with the findings of the previous study by Sato et al investigating the effects of the ERβ Rsa polymorphism on RA [14]. Furthermore, in this study, we found that the OA patients were older than the RA patients, which is perhaps not surprising given that OA pathologic features is closely associated with aging.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because this evaluation is primarily dependent on the stages and progress of joint deterioration (e.g., mild or rapid, and oligo arthritis or multi joint), classifications of disease severity are not influenced by differences in sensitivity to drug treatment. Most of the patients enrolled in this study were classified as MES RA, which was consistent with the findings of the previous study by Sato et al investigating the effects of the ERβ Rsa polymorphism on RA [14]. Furthermore, in this study, we found that the OA patients were older than the RA patients, which is perhaps not surprising given that OA pathologic features is closely associated with aging.…”
Section: Discussionsupporting
confidence: 90%
“…These severity classifications were determined by orthopedic specialists based on long-term observation data. Most of the patients in the study were classified as MES, similar to those in our previous study [14]. Figure 1 shows the frequency distribution of the CA repeats in the RA and OA patients.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In stark contrast to SLE, RA is most prevalent in post-menopausal women [133] with peak incidence of onset of RA observed at menopause [138]. Polymorphisms in the ERa have been linked to age of onset of RA [139], and a polymorphism in the ERb may be associated with severity of RA and female prevalence [140]. Viewed altogether, these data suggest that hormones are protective in RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 95%
“…The rs1256120 SNP was evaluated as a potential genetic marker predicting the outcome of brace treatment in patients with adolescent IS however, no association was found. 16 Two other SNPs in ESR2 (rs4986938 and rs1256049) were described to have association with multiple diseases, especially with breast cancer, 19 prostate cancer, 20 male infertility, 21 obesity in women, 22 rheumatoid arthritis, 23 bone mineral density, and 24 , 25 endometriosis. 26 However, the SNPs association with IS has not been evaluated.…”
mentioning
confidence: 98%